Digitaler Euro: Hohe Kosten bei nicht erkennbaren Vorteilen - Peter Bofinger (Wirtschaftsdienst, 2023)
– The ECB has embarked on an uncertain path with the digital euro project. It is pursuing a strategy that is unclear about whatproblems it is trying to solve and what specific goals it is trying to achieve. The ECB has not yet been able to diagnose a clear marketfailure that would justify such far-reaching government intervention. The attempt to claim the need for a "monetary anchor" instead isnot very convincing. The current design is unlikely to attract much interest from citizens and thus will not contribute to greater Europeanstrategic autonomy in the payment system. This requires a solution that does not rely on system-specific balances and is therefore moreconvenient, while simultaneously avoiding impending risks to the financial system.
Keywords: E40; E50; G20; 330; Euro; Virtuelle Währung; Zahlungsverkehr; Euro; Virtuelle Währung; Zahlungsverkehr